Beneficial effects of potassium iodide incorporation on grain boundaries and interfaces of perovskite solar cells. Issue 49 (10th September 2019) - Yang, Yin; Wu, Lili; Hao, Xia; Tang, Zeguo; Lai, Huagui; Zhang, Jingquan; Wang, Wenwu; Feng, Lianghuan
Abstract : The improved performance for KI incorporated perovskite solar cells are clarified from the point view of grain boundry and interface passivation. Abstract : Grain boundaries and interfacial impurities are the main factors that limit the further development of polycrystalline perovskite solar cells because their existence severely deteriorates the device performance. In order to optimize the efficiency of perovskite solar cells, it is essential to eliminate these defects. In the present work, potassium iodide (KI) is incorporated into the perovskite absorber. KI incorporation improves the crystallinity of the perovskite, increases the grain size, and decreases the contact potential distribution at the grain boundary, which are verified by X-ray diffraction, scanning electronic microscopy and Kelvin probe force microscopy. Besides, the activation energy of the recombination, estimated from the temperature dependent current–voltage of perovskite solar cells, is larger than the bandgap calculated from the temperature coefficient. These suggest that KI incorporation effectively passivates the grain boundaries and interfacial defects. As a result, charge trapping in the absorber as well as the bimolecular and trap-assisted recombination of the device are significantly suppressed. Consequently, the open circuit voltage and fill factor of the incorporated devices are greatly improved, enabling an optimized power conversion efficiency of 19.5%, in comparison with that of 17.3% for the control one. Our work provides an effective strategy of defect passivation in perovskite solar cells by KI incorporation and clarifies the mechanism of the performance optimization of KI incorporated devices.